Technological Education, Training and Process Identity - Nikolaevich Romanov, Nikolay (2020)
The paper presents the results of the analysis of technological education, namely the identification of educational technology and the technological process. It was found that most major technology creators transform both their ideas and their techniques into modern technological operations as well as educational technologies. The authors propose that the training process may be regarded as technological in nature and the one that embraces the same methods of analysis (including activity approaches). In other words, the analysis of the educational process is identical to the analysis of technological process. In methodological terms, the closest to that step sequence is project-based learning. The conclusion is reached by drawing on the analysis of training processes in general and on the analysis of operational training in particular including the step-by-step performance of certain technological operations.